Association between glucosinolate concentration and injuries caused by cabbage stink bugs Eurydema spp. (Heteroptera: Pentatomidae) on different Brassicas - doi: 10.4025/actasciagron.v35i1.15622 - Tanja Bohinc; Robert Hrastar; Iztok Jože Košir; Stanislav Trdan (Acta Scientiarum. Agronomy, 2012)
In 2010, we were determining the contents of glucosinolates in different Brassicas in order to study their influence on feeding of cabbage stink bugs (Eurydema spp.) and the consequent extent of damage. We confirmed that glucosinolates content depends on plant species, plant organs and the time of sampling. In the samples aliphatic glucosinolates (glucoiberin, progoitrin, epiprogoitrin, epiprogoitrin, sinigrin, gluconapin, glucoraphenin, sinalbin) prevailed. Glucobrassicin, an important indolic glucosinolate compound, was detected in all tested Brassicas. Its concentration in the oil radish samples was highest during the first assessment (30 DAS), 8.84 ± 0.65 µmol g-1 ds, while the oilseed rape samples displayed lowest concentration during the last assessment (134 DAS), 4.30 ± 0.80 µmol g-1 ds. The stimulative activity of individual glucosinolates or their negative influence on feeding of cabbage stink bugs in the Brassicas used in our experiment was not uniformly manifested. Based on a two-year field experiment we concluded that oil rape was the most adequate trap crop used to allure cabbage stink bugs. In future, glucosinolates should be employed to a greater extent in environmentally acceptable ways of food production, one of which is also the use of trap crops in order to reduce harmful effects of cabbage stink bugs.